2002
DOI: 10.1590/s1020-49892002000200006
|View full text |Cite
|
Sign up to set email alerts
|

Peruvian mothers' knowledge and recognition of pneumonia in children under 5 years of age

Abstract: Although the percentage of mothers believing they can recognize pneumonia through rapid breathing and chest retraction seems to have increased in recent years, there is still a sizable percentage of mothers who remain uninformed about pneumonia and its possible fatal consequences. Efforts need to continue to educate Peruvian mothers about the causes, recognition of the signs, and treatment of pneumonia. The results suggest that the Government of Peru pneumonia campaign should use television much more, as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 13 publications
3
16
0
Order By: Relevance
“…The seeming low awareness of pneumonia among the rural dwellers of Dangme West district is consistent with earlier findings of studies conducted in Eastern Uganda among mothers and traditional healers [22] but in contrast to the findings in Kenya [16], Pakistan [15], Peru [17] and Western Uganda [23], where participants had heard about the illness and were easily able to identify the signs and symptoms. It can therefore be posited that such problems of low awareness are community specific, and may be dependent on the linguistic interpretation of diseases and how they may be perceived within the communities.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The seeming low awareness of pneumonia among the rural dwellers of Dangme West district is consistent with earlier findings of studies conducted in Eastern Uganda among mothers and traditional healers [22] but in contrast to the findings in Kenya [16], Pakistan [15], Peru [17] and Western Uganda [23], where participants had heard about the illness and were easily able to identify the signs and symptoms. It can therefore be posited that such problems of low awareness are community specific, and may be dependent on the linguistic interpretation of diseases and how they may be perceived within the communities.…”
Section: Discussionsupporting
confidence: 88%
“…As they had more knowledge on the causes of pneumonia, they considered doing the opposite of the causative factor, as a form of treatment [17]. For instance, “ If cold temperature was indicated as one important cause of pneumonia, then making the child sweat or providing heat will bring health.” As a result, Peruvians explored practices like sauna, spa and thermo therapeutic methods as a ways of treating some ARIs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several of the included studies suggest that health education programmes can improve caregiver recognition of childhood illness and appropriate care seeking. A cross-sectional study in Peru [57] found that mothers who reported to have been exposed to a national pneumonia educational campaign on television were more likely to select rapid breathing and chest retraction as signs of pneumonia in a questionnaire. In addition, a before-and-after evaluation [58] of community information activities and a training of trainers for leaders of women groups in Nigeria found significant improvements in knowledge of the symptoms of malaria and its treatment, increased rates of appropriate care seeking for severely ill children, and reductions in rates of consultations with traditional healers for severely ill children (from 60% to 6.7% of cases).…”
Section: Discussionmentioning
confidence: 99%
“…7 8 Previous studies from developing regions of the world where the burden of pneumonia is high have documented that mothers' knowledge of the common features of pneumonia is low. [9][10][11] As part of a programme of events during the year 2011 World Pneumonia Day, the Paediatric Association of Nigeria (PAN) undertook the present study to document mothers' knowledge about the common features, major risk factors and causes of childhood pneumonia. The findings of the study would guide the development of campaign resources for public enlightenment about community acquired childhood pneumonia.…”
Section: Introductionmentioning
confidence: 99%